Analysis of the Implementation of Corporate Social Responsibility of PT. Pertamina Fuel Terminal Donggala - Anggie Tia Sari; Burhanuddin Burhanuddin; Haris Abd. Kadir (Universitas Muhammadiyah Palu, 2021)
PT. Pertamina (Persero) Fuel Terminal Donggala as a communicator provides understanding and understanding to the community in the company environment showing its existence or presence as part of the community in the Donggala area to grow and develop in line with the development of PT. Pertamina (Persero) Fuel Terminal Donggala. PT. Pertamina (Persero) Fuel Terminal Donggala has a goal to affect corporate social responsibility (CSR) recipients positively. The research objective was to identify and analyze the implementation of Corporate Social Responsibility (CSR) of PT. Pertamina Fuel Terminal Donggala. The results showed that the Corporate Social Responsibility (CSR) program at PT. Pertamina Fuel Terminal Donggala runs optimally by the PT. Pertamina focuses on four pillars, namely green Pertamina, intelligent Pertamina, independent Pertamina, and healthy Pertamina.